The Influence of Entrepreneurship Knowledge, Industrial Work Practice and Self-Efficacy on Entrepreneurial Interest of Class XII BDP Students - Khirat, Miftahul; Asriati, Nuraini; Syamsuri, Syamsuri; Syahrudin, Hunsi; Basri, M. (Education Achievement: Journal of Science and Research, 2024)
This study aims to examine and analyze the Effect of Entrepreneurship Knowledge, Industrial Work Practice and Self-Efficacy on Entrepreneurial Interest of Class XII BDP Students of SMKN 8 Pontianak. This form of research is Quantitative research with Survey research type. The sample in this study were XII BDP class students 83 students. The sampling method is Total Sampling population The results showed that 1. There is a significant effect of X1 Entrepreneurship Knowledge on Y Entrepreneurial Interest indicated by a significant value of 0.000. The calculated t value of 12.809 is greater than the t table of 1.664 by having an influence of 66.9%, 2. There is a significant effect of X2 Industrial Work Practice on Y Entrepreneurial Interest indicated by a significant value of 0.018, with a calculated t value of 2.414 having an influence of 6.7%, 3. There is a significant effect of X3 Self-Efficacy on Y Entrepreneurial Interest indicated by a significance value of 0.000. There is an effect of Entrepreneurship Knowledge (X1), Industrial Work Practice (X2), and Self- Efficacy (X3) has a positive influence on Entrepreneurial Interest (Y) together (simultaneously) with a significance value of 0.000 smaller than 0.005 with a value of F value calculated 82.734 greater than F table 2.76 with the influence of 75.9%.